Pemeliharaan Komitmen pada Pasangan Pernikahan Dini - Kurnia Primareta; Joyo Nur Suryanto Gono (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
This study sees that early marriage is still prevalent in Indonesia with various backgrounds, even though early marriage has many risks such as domestic violence or divorce caused by differences in forms of communication between husband and wife that cannot be managed due to immature age or other things. Others, leading to divorce. The purpose of this study is to analyze the management of the communication process between married couples in early marriage, when there are contradictions in the different forms of communication that occur in everyday household life with the aim of maintaining and maintaining the commitments that have been built. This research is a descriptive study using relational dialectical theory, commitment theory, and naturalistic paradigm. The data collection technique used by the researcher is indepth interviews. The results of the study prove that early marriage couples who marry with various backgrounds experience relational dialectical contradictions due to different forms of communication. The three pairs experience three main contradictions in relational dialectics, namely integration and separation, stability and change, and expression and non-expression. In managing different forms of communication, the three early married couples feel that age affects them to overcome prestige, influences to listen to their partner's opinions and requires the intervention of others. However, this can be done by taking a special time that is fun so that the couple can express their feelings to each other and understand each other in a relaxed atmosphere.